Optimization of Anthocyanin Extraction Process in Pacar Air (Impatiens balsamina) Flower from Canang Sari Flower Waste - Audina Setya Fitriana; Edia Rahayuningsih; Rochim Bakti Cahyono (ALCHEMY Jurnal Penelitian Kimia, 2025)
Canang sari is one of the offerings used in Hindu worship in Bali, consisting of various types of flowers, one of which is Impatiens balsamina Currently, the waste of canang sari flowers has not been utilized optimally. Pacar air (Impatiens balsamina) flower waste contains anthocyanin compounds and gives a purplish red color, which is promising as a natural dye raw material. This research aims to conduct phytochemical tests and determine the optimum operating conditions for extracting natural dyes from Pacar air (I. balsamina) flowers obtained from canang sari. The extraction of I. balsamina flowers uses acetone and ethanol solvents. Phytochemical, gravimetric, and UV-VIS spectrophotometric tests were conducted to determine the chemical content and stability. The extraction process is optimized using the Response Surface Methodology with Central Composite Design (CCD) type. The independent variables in this extraction process are: pH 1 – 4, temperature 40 – 70 ℃, and extraction time 5 – 60 minutes, while the dependent or response variable is anthocyanin content. The control variables of this extraction process are the ratio of materials and solvents of 0.0625 g/mL, and the stirring speed of 300 rpm. As a result, the optimum operating conditions of the extraction process are pH 2.84, temperature 63.85 ℃, and time 16.15 minutes, with anthocyanin levels of 18.05 mg/L.